2022
DOI: 10.3389/fvets.2022.935939
|View full text |Cite
|
Sign up to set email alerts
|

Rumen-protected zinc–methionine dietary inclusion alters dairy cow performances, and oxidative and inflammatory status under long-term environmental heat stress

Abstract: Dairy cows are susceptible to heat stress due to the levels of milk production and feed intake. Dietary supplemental amino acids, particularly rate-limiting amino acids, for example, methionine (Met), may alleviate the potential negative consequences. Zinc (Zn) is beneficial to the immune system and mammary gland development during heat stress. We investigated the impact of a source of a rumen-protected Zn-Met complex (Loprotin, Kaesler Nutrition GmbH, Cuxhaven, Germany) in high-producing Holstein cows during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…However, most published studies on this issue have primarily focused on its effects on lactating cows [21], calves, and heifers [22]. They have also explored the effectiveness of feed additives in mitigating the negative consequences of HS [23,24], as well as changes in farm management, including the implementation of cooling systems like a combination of ventilation and water spraying, especially during lactation [25]. Additionally, limited scienti c data are available on the carry-over effects of HS occurrence de ned by the THI during the close-up period, which is a critical time for highyielding dairy cows during the transition period, on productive performance, fertility, and immunometabolic status during the subsequent lactation.…”
Section: Discussionmentioning
confidence: 99%
“…However, most published studies on this issue have primarily focused on its effects on lactating cows [21], calves, and heifers [22]. They have also explored the effectiveness of feed additives in mitigating the negative consequences of HS [23,24], as well as changes in farm management, including the implementation of cooling systems like a combination of ventilation and water spraying, especially during lactation [25]. Additionally, limited scienti c data are available on the carry-over effects of HS occurrence de ned by the THI during the close-up period, which is a critical time for highyielding dairy cows during the transition period, on productive performance, fertility, and immunometabolic status during the subsequent lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the findings of this study demonstrated that feeding rumen-protected zincmethionine to animals during times of heat stress could maintain their ability to produce milk and the composition of their milk. Animals' improved performance after taking Zn-Met complex supplements may have improved oxidative and immune status [33]. Supplementing multiparous lactating Holstein with 35 mg of Zn/kg of DM from Zn hydroxy chloride and 40 mg of Zn/kg of DM from Zn-Met complex had a significant impact on mammary cell turnover [34].…”
Section: Zincmentioning
confidence: 99%
“…It was involved in various physiological processes, such as DNA methylation, protein synthesis, and antioxidant balance [ 10 ]. Previous studies conducted in dairy cow observed that supply of Met altered the synthesis of low-density lipoproteins (VLDL), thereby inhibiting the accumulation of triacylglycerol in the liver [ 11 ]. Thus, to maintain a protein-amino acid balance, essential amino acids should be supplemented when decreasing the levels of dietary protein while diminishing dietary protein [ 12 ].…”
Section: Introductionmentioning
confidence: 99%